ANALISIS UNSUR BATIN DALAM PUISI “KONTEMPLASI” KARYA IKA MUSTIKA - Setiawan, Sandi (IKIP Siliwangi, 2020)
Literary works are not only meant as works that have beauty in each string of words, but every literary work contains meaning or meaning that can be felt by living it. Poetry is one form of fiction that implies meaning. Poetry can be a motivation for lovers of writing, especially for readers who want to know the meaning or meaning contained in a poem. The author is interested in analyzing the inner elements of poetry contained in a poem by Ika Mustika entitled